3‐T proton magnetic spectroscopy in unmedicated first episode psychosis: A focus on creatine. Issue 3 (17th April 2012) - Tibbo, Philip G.; Bernier, Denise; Hanstock, Christopher C.; Seres, Peter; Lakusta, Bonnie; Purdon, Scot E.
Abstract Different lines of evidence suggest an abnormal cerebral energy metabolism as being critical to the pathophysiology of schizophrenia. However, it is unknown as to whether levels of creatine (Cr) would be involved in these anomalies. The study involved 33 unmedicated first episode psychosis patients and 41 healthy controls. Proton magnetic resonance spectroscopy (1H‐MRS) was performed at 3 T using a long TE (TE/TM/TR of 240/27/3000 ms) such that within the total phosphocreatine (PCr) plus Cr signal (tCr240), mainly Cr was detectable. The target region was an 18 cm3 prefrontal volume. A negative association was found between age of patients and tCr240 levels referenced to internal water, with 20% of the variance in tCr240 accounted for by Age. A secondary finding revealed 16% reduction of tCr240 levels in patients, solely when comparing participants older than the median age of patients. No association existed between tCr240 levels and clinical variables. These findings support previous data reporting abnormalities in brain creatine kinase isoenzymes involved with the maintenance of energy pools in schizophrenia. The implications of using a long TE are discussed in terms of the relative proportions of Cr and PCr within the tCr240 signal, and of potential group differences in T2 times. Magn Reson Med, 2013. © 2012 Wiley Periodicals, Inc.